2005
DOI: 10.1002/bjs.5048
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing regional and general anaesthesia in minimally invasive video-assisted parathyroidectomy

Abstract: MIVAP performed under RA was associated with a shorter overall operating time and a reduced need for postoperative pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…Its low invasiveness and the similarity with the conventional procedure render this approach feasible also under locoregional anesthesia (cervical block) [30,31] , at least in selected patients, with the benefit of avoiding the major side effects of general anesthesia. Moreover, it has been demonstrated that locoregional anesthesia allows for a significant reduction of operating room occupation time and it is associated with significantly less postoperative pain [31] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its low invasiveness and the similarity with the conventional procedure render this approach feasible also under locoregional anesthesia (cervical block) [30,31] , at least in selected patients, with the benefit of avoiding the major side effects of general anesthesia. Moreover, it has been demonstrated that locoregional anesthesia allows for a significant reduction of operating room occupation time and it is associated with significantly less postoperative pain [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that locoregional anesthesia allows for a significant reduction of operating room occupation time and it is associated with significantly less postoperative pain [31] . As for other targeted approaches, it could be performed as an outpatient and/or same day procedure, at least in selected cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter method, a deep bilateral cervical plexus block is required with anesthetic infiltration of the wound area [13,14] . The patient lies in a supine position with his neck not hyperextended.…”
Section: Techniquementioning
confidence: 99%
“…Nevertheless, with the variable number and anatomic location of parathyroid glands, preoperative imaging has rarely been used for traditional open-neck surgery [8][9][10][11]. Since 90 % of patients with PHPT have a single gland adenoma, minimally invasive parathyroidectomy (MIP) was introduced [12][13][14], with decreased intraoperative time, size of surgical incision and complication rates [15,16]. Accurate preoperative localisation of parathyroid disease is absolutely critical for effective surgical treatment when MIP is used [17,18], and almost all authors also recommend intraoperative PTH hormone level monitoring [19][20][21].…”
Section: Introductionmentioning
confidence: 99%